Object-Oriented Analysis and Design with Applications - Grady Booch, Robert A. Maksimchuk and Michael W. Engle (Pearson Education, 2008)
The previous editions of this book have taught tens of thousands how to apply the concepts and ideas behind object technology to design successful software applications. This revision will bring the book up to date with the many changes in technology tha